Behavior of the physical and physicochemical characteristics of bacuri pulp submitted to processing to obtain foam and powder (Research, Society and Development, 2022)
Bacuri is an Amazonian fruit with nutritional and functional potential. Such characteristics confer high perishability to the fruits. The drying of food products has been a principle to increase shelf life, as well as an alternative to the lack of market and high cost of storage. Thus, this work aimed to study the physical and physical-chemical characteristics of bacuri pulp in natura and elaborate foam, as well as to evaluate the physical and physical-chemical characteristics of the powders obtained by drying in a foam layer at temperatures of 50, 60 and 70°C. The foam was made from fresh pulp diluted in 50% water and addition of 2.5% of Emustab and 5.0% of Albumin for 15 minutes of agitation in a domestic planetary mixer, then subjected to to the drying process. To characterize the products, the water content, pH, acidity, lipids, total sugars, reducing sugars and non-reducing sugars were evaluated. For the color parameters L*, a* and b*, the Colorimeter version 5.5.1 was used. The process of converting bacuri pulp into foam causes a difference in some physical and physical-chemical attributes, and drying at 70 ºC is better suited to the phenomenon, consolidating the foam layer drying technique as a simple and effective method for development on an industrial scale.